Enforcement Of Islamic Family Law In Review Of Supreme Court Jurisprudence - Alfiansyahputra Alfiansyahputra (International Asia Of Law and Money Laundering (IAML), 2022)
The Contra opinion on the jurisprudence of the Supreme Court judge on Islamic family law greatly interferes with the existence of the enforcement of justice, because the legal basis is often contrary to the text of legislation. The study analyzed whether and to what extent the jurisprudence of the Supreme Court can enforce Indonesian Islamic Family Law. This type of research is library research, data needed secondary data. The approach method is doctrinal juridical, and the data is analyzed qualitatively. The research product explains that MA jurisprudence is one of the products of Islamic legal thought from the judiciary, judges play an important role in enforcing Islamic law because judges cannot be separated from ijtihad to find law through understanding and meaning of the law. The existence of jurisprudence is used as the basis for legal considerations of PA judges in resolving cases, able to strengthen the strengthening of law and solving problems of Islamic family law fairly and correctly based on the basic principles of Islamic Sharia.